Wybor poezyj - Mickiewicz, Adam, 1798-1855.; Zgorzelski, Czeslaw (Wroclaw : Zaklad Narodowy im. Ossolinskich, 1986)
Selected poetry by the noted Polish national poet.
Vol. 2: Wyd. 3., zmienione.
Includes bibliographies.
Keywords: Polish poetry -- 19th century